Optimalisasi Pemanfaatan Bunga Telang sebagai Produk Unggulan Desa Sumberwaru bersama Ibu PKK - Rahmawati, Dewi; Anggrelia, Tarizza Puspa; Ambari, Yani; Ningsih, Arista Wahyu; Aristia, Bella Fevi; Klau, Ivan Charles Seran (Jurnal Abdi Masyarakat (JAM), 2025)
In Indonesia, butterfly pea flowers are known as ornamental and medicinal plants with various benefits. Utilization of natural potential as a superior village product is a strategic step in improving community welfare and the local economy. Sumberwaru Village has superior natural resources, one of which is butterfly pea flowers (Clitoria ternatea L.). This community service aims to optimize the utilization of butterfly pea flowers (Clitoria ternatea L.) as a superior product in Sumberwaru Village through education and demonstration programs for PKK mothers. The methods used in this study were 1) implementation, community service activities began with the provision of materials related to the utilization of butterfly pea flowers, 2) evaluation, conducted by comparing the average scores before and after the test to measure the increase in participants' knowledge. The results of the activity showed that education succeeded in increasing community knowledge by 41.08%, with an average pre-test and post-test value of 51.89% and 92.97%. The evaluation results showed that the utilization of butterfly pea flowers can be a strategic step in developing village potential and increasing community participation in local economic activities.